Pericapsular Nervous Group Block versus Suprainguinal Fascia Iliaca Block Using the Same Injection Volume in Primary HIP Arthroplasty Prospective Observational Study - Luis Baeza Álvarez; José Manuel López González; Gustavo Illodo Miramontes; Bárbara María Jiménez Gómez; María Vega Colon; Alejandra Williams Aguirre; Pablo Casas Reza; Servando López Álvarez; Shu-Wei Liao; Bing-Ying Ho; Meng-Ta Yang; Jin-De Hou; et al. (International Journal of Clinical Practice)
Objectives. To determine the pericapsular nerve group (PENG) block’s postoperative analgesic efficacy and safety compared to the suprainguinal fascia iliaca (SFI) block in patients undergoing primary hip arthroplasty using the same injectate volume. Material and Methods. Between January 2021 and March 2022, American Society of Anesthesiologists Physical Status (ASA-PS) classification I–III patients scheduled for hip arthroplasty were included in this study. After standard monitoring and subarachnoid anesthesia, an ultrasound-guided PENG or SFI block with 20 ml of 0.25% levobupivacaine was performed for postoperative analgesia. All patients were assessed with a numerical rating scale (NRS) at presurgery, upon arrival at the postanesthesia care unit (PACU), and in the postoperative period at 2, 4, 12, and 24 hours. The need for analgesic rescue and adverse effects was also assessed. Results. A total of 130 patients were included in the study (62 PENG block and 68 SFI block). Both blocks were equally effective in managing postoperative pain without any statistically significant differences except at 12 h (p=0.023), where the deviation found was not clinically relevant. The median total morphine consumption was 0 mg [0–2] in the PENG block group and 0 mg [0–2] in the SFI block group. A more significant motor block was found in the first 6 hours in the SFI block group (p=0.001). There was no significant difference in the ease of performing PENG (79%) or SFI (85%) blocks. No major complications were recorded in both groups, and patient satisfaction was high (83.9% for the PENG block group vs. 91.2% for the SFI block group). Discussion. Both blocks have been demonstrated to be effective for postoperative analgesia in hip arthroplasty and should be integrated as a multimodal analgesic strategy. The lesser degree of motor block recorded in the first hours with the PENG block makes it the most suitable option for early recovery. Both techniques were easy and safe to perform.